Interaction between Judaism and Christianity in history, religion, art and literature - Poorthuis, Marcel, 1955-; Schwartz, Joshua.; Turner, Joseph. (Jewish and Christian Perspectives Series, 2009)
This volume contains a variety of essays that deal with the complex relationships between Judaism and Christianity. From the Jewish side, particularly in Orthodox circles, there is a position maintaining the independence of Judaism from outside influences including Christianity. Traditional Christian theology, on the other hand, held a supercessionist view in which Judaism was seen merely as a historical preparation for the later revelation of Christianity. Was there no real interaction? When and how did Judaism and Christianity become two distinct religions? When did the 'parting of ways\' take place, if indeed there really was such a parting of ways? The present volume takes a bold step forward by assuming that no historical period can be excluded from the interactive process between Judaism and Christianity, conscious or unconscious, as a polemical rejection or as tacit appropriation.